End-Stage Renal Disease From Cast Nephropathy in a Teenager With Neuroendocrine Carcinoma. Issue 5 (July 2016) - Butani, Lavjay; Ducore, Jonathan
Abstract : Cast nephropathy is the most common manifestation of renal injury in patients with multiple myeloma but is rarely reported in other conditions. We are reporting our experience in caring for a teenager with a metastatic neuroendocrine carcinoma who developed rapidly progressive kidney injury that advanced to end-stage renal disease. On renal biopsy extensive tubular necrosis and intratubular eosinophilic casts were noted. This previously unreported finding should prompt oncologists to closely monitor for such a complication in patients with secretory tumors. Whether early plasmapheresis could be of benefit, as has been tried in multiple myeloma, remains to be determined.